Diversity of endophytic fungi in triphala trees of achanakmar-amarkantak biosphere Reserve chhattisgarh - AMIT SHARMA (International Journal of Pharma and Bio Sciences, 2017)
Endophytic fungi are a group which resides within the living tissues of the host plant without producing any apparent disease or disease-like symptoms. Triphala trees such as T. chebula, T. bellerica and Emblica officinalis are important traditional medicinal plants were taken to carry out the studies on endophytic fungi. The forest of central India is basically a tropical semi-evergreen Sal forest. Chhattisgarh state in central India is well recognized for maximum area of forests. The state is also known for maximum varieties of tree species most of which are of pharmaceutical importance. In the present study the above mentioned tree species were screened for the presence of endophytic fungi. The samples were collected from the Achanakmar–Amarkantak Biosphere Reserve in the winter, summer and rainy season. The seasonal occurrence and distribution of endophytic fungi were recorded. In present investigation Pestalotiopsis and Colletotrichum sp. were found frequently in leaf samples of Bahera, whereas Alternaria sp. and Phyllosticta sp. were often encountered in Harra tree. Despite the specificity of tree plants, the study reveals importance of the geographical and seasonal factors with respect to the presence or absence of endophytic fungi.